Comparing the effectiveness of selective laser trabeculoplasty with topical medication as initial treatment (the Glaucoma Initial Treatment Study): study protocol for a randomised controlled trial. Issue 1 (December 2015) - Lamoureux, Ecosse; Mcintosh, Rachel; Constantinou, Marios; Fenwick, Eva; Xie, Jing; Casson, Robert; Finkelstein, Eric; Goldberg, Ivan; Healey, Paul; Thomas, Ravi; Ang, Ghee; Pesudovs, Konrad; et al.
Abstract Background Glaucoma is the leading cause of irreversible blindness in the world. Estimated to affect 60 million people worldwide, this figure is expected to rise to 80 million by 2020. Untreated, glaucoma leads to visual decay and eventually to blindness, and can significantly reduce quality of life. First-line treatment in patients with primary open-angle glaucoma and exfoliative glaucoma is topical medical therapy with ocular hypotensives as eye drops. However, eye drops have several disadvantages including cost, possible local and systemic side effects, and adherence and perseverance issues. Randomised controlled trials have demonstrated that selective laser trabeculoplasty is equally as effective in lowering intraocular pressure as eye drops. However, the impact of these two treatment modalities from the patient and economic perspectives has not been adequately determined. Thus, it remains unclear whether topical medical therapy or selective laser trabeculoplasty should be recommended as first-line treatment for glaucoma. Methods/Design This protocol describes an international, multi-centre, randomised controlled trial to determine the optimum first-line therapy for people with primary open-angle glaucoma and exfoliative glaucoma. This study will compare the effect of selective laser trabeculoplasty and topical medication with respect to patients' generic and glaucoma-specific quality of life. The trial will also provide a detailed cost-effectiveness analysis and compare the clinical effectiveness with respect to the degree of intraocular pressure lowering and rates of treatment failure. Research coordinators in each centre will identify and recruit previously untreated patients with primary open-angle glaucoma and exfoliative glaucoma. Those who meet the eligibility criteria will be invited to enter a randomised controlled trial with either selective laser trabeculoplasty or topical ocular hypotensive therapy, according to a stepped regimen. Outcome assessment will be measured at 6 weeks and at 6, 12, and 24 months post-treatment. Regular clinic follow-ups will continue as clinically indicated between study outcome visits. Discussion The Glaucoma Initial Treatment Study is the first multi-centred RCT to determine the optimum first-line therapy for people with glaucoma. Our trial will have an unprecedented capacity to meaningfully transform the treatment and management of glaucoma in Australia and overseas. Trial registration ACTRN12611000720910 ; Date registered: 11 July 2011